Analisis Konten Strategi Komunikasi Visual Ustadz Hanan Attaki dalam Dakwah Digital melalui Instagram - Ramdani, Riska (Neolectura, 2025)
Instagram is a social media platform with a large user base, boasting 1.4 billion active monthly users. This platform is utilized, among other things, for visual communication in digital preaching by Ustadz Hanan Attaki through his Instagram account @hananattaki. The purpose of this study is to understand the visual communication strategies employed by Ustadz Hanan Attaki on his Instagram account. The research method used is qualitative and descriptive in nature. The results of the study show that Ustadz Hanan Attaki has successfully implemented visual communication strategies on Instagram, creating a positive impact in spreading Islamic messages. This study is expected to provide insights into the importance of visual communication in digital preaching and to inspire preachers to develop their skills in the digital era.